2021
DOI: 10.3390/medicina57121372
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Global and Regional Longitudinal Strain for Clinical Assessment of HFpEF in Coronary and Hypertensive Patients

Abstract: Background: Contribution of global and regional longitudinal strain (GLS) for clinical assessment of patients with heart failure with preserved ejection fraction (HFpEF) is not well established. We sought to evaluate subclinical left ventricular dysfunction secondary to coronary artery disease (CAD) in HFpEF patients compared with hypertensive patients and age-matched healthy subjects. Material and methods: This was a retrospective study that included 148 patients (group 1 = 62 patients with HFpEF, group 2 = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Six studies[20,23,27,3133] estimated the diagnostic usefulness of LV GLS values in HFpEF compared with healthy controls, with LV GLS cut-off values ranging from -16% to -24.1 and AUC from 0.68 to 0.98 (Table 2). Five trails provided complete data for diagnostic meta-analysis (SEN, SPN, TP, FP, FN, and TN).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies[20,23,27,3133] estimated the diagnostic usefulness of LV GLS values in HFpEF compared with healthy controls, with LV GLS cut-off values ranging from -16% to -24.1 and AUC from 0.68 to 0.98 (Table 2). Five trails provided complete data for diagnostic meta-analysis (SEN, SPN, TP, FP, FN, and TN).…”
Section: Resultsmentioning
confidence: 99%
“…The initial search produced 103 studies and with one identified through other sources, 104 studies were screened and then relevant studies were assessed and evaluated for inclusion (Figure 1). Eight studies were included for quantitative synthesis (Table 1) [17,[19][20][21][22][23][24][25][26]. Excluded were studies that focused on HFpEF in animal models [23].…”
Section: Resultsmentioning
confidence: 99%
“…GLS is widely used in the field of cardiology generally, where it has demonstrated value in detecting subtle myocardial dysfunction, diagnosing disease, predicting disease progression, and allowing for early pharmacological intervention. GLS has demonstrated its usefulness in a number of cardiac diseases, including cardiomyopathy, myocardial infarction, HF, hypertension, and acute coronary syndrome [ 31 , 32 , 33 , 34 ]. Correlations between GLS and deleterious myocardial changes, prognostic predictors, and cardiovascular outcomes have been established in various diseases [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Lsmentioning
confidence: 99%
“…GLS has demonstrated its usefulness in a number of cardiac diseases, including cardiomyopathy, myocardial infarction, HF, hypertension, and acute coronary syndrome [ 31 , 32 , 33 , 34 ]. Correlations between GLS and deleterious myocardial changes, prognostic predictors, and cardiovascular outcomes have been established in various diseases [ 31 , 32 , 33 , 34 , 35 , 36 ]. Therefore, it is not surprising that GLS assessment is recommended in the current cardio-oncology guidelines of the European Society of Cardiology [ 18 ].…”
Section: Lsmentioning
confidence: 99%